Productivity indicators and market structure in entry and exit models of Iranian manufacturing sectors - Chahaki, Hamid Reza Morad Pour (2013)
The decision and the timing of entry and exit are sensitive to condition and cyclical disturbances which are neglected in the Iranian manufacturing sector. The lack of entrants‟ paying attention to productivity conditions as main determinants of entry is resulted in wastage of resources and growth instability in the manufacturing sector. Iranian authorities of manufacturing sector do not pay much attention to the importance of entry condition; market structures, entry barriers as well as entry incentives and productivity measures. They facilitate the conditions of entry to the industry without paying attention to the ability of entrants, market potential, market structure, and scarcity of natural resource. Basically, entry is an investment behavior that involves long-term decision.This study attempts to evaluate the structure of the Iranian manufacturing industry by studying estimations of productivity indexes, entry and exit phenomena in the manufacturing sector as a whole, as well as capital and labour intensive sub sectors during the time period of 1997-2006. This study covers five models; three of which deal with industry productivity and the other two focus on entry and exit decisions. In the first three models, variables that act as performance indicators in productivity equations are growth rate of demand, capital output ratio, investment sale ratio, advertising intensity and minimum efficiency scale (MES). The idea being, the productivity and behavior of firms is based on performance indicator, will predict whether they will be able to continue in market route or not. The fourth and fifth models take into account the impacts of incentives, barriers, economic conditions and productivity indicators on entry and exit phenomena. Moreover, it included testing on displacement and replacement effects by considering lagged entry rate and lagged exit rate in the exit and entry equations, respectively. Ultimately, we arrive at a causality relationship between entry and exit rates in Iran‟s manufacturing industry by adding current entry or exit rate in the exit or entry equations and estimating both equations in simultaneous equation system. The results of this study reveal several noteworthy findings. While evaluating productivity, it was found that the productivity indexes are highly sensitive to investment sales ratio. The negative and significant coefficients of the investment sale ratio confirm that structures in the manufacturing industry are not suitable for high volume of investment. In addition, minimum efficiency scale as an entry barrier causes increases in profit which result in improvements in labour productivity and labor-capital expenditure productivity. Analysis of the entry and exit equations, found that in the labour intensive sub sectors factors like profit, advertising, productivity indexes are significant in the estimation of the entry model. Alternatively, advertising, concentration, and productivity indexes are the only significant factors in the exit model. Furthermore, in capital intensive sub sector profit and concentration were detected as significant variables in entry model as well as significant of GDP in exit model. Finally, the one-way causality relationship is accepted in 2SLS and 3SLS models. In conclusion, knowledge of the variables that influence the productivity indexes and entry and exit phenomena is valuable to policy makers in structuring the Iranian manufacturing sector. They should design a proper policy framework in addressing the identified problems of the industry as well as optimizing the use of capital tools. They should also pay attention to the importance of entry condition; market structures, entry barriers, entry incentives, and productivity measures. Finally, Iranian manufacturing sector will have a stable entry growth, however, this will depend on paying attention to the ability of entrants, market potential and scarcity of resource.